Historical Review of the I. I. Mechnikov Institute of Microbiology and Immunology of the National Academy of Medical Sciences of Ukraine - Minukhin, Valery; Rezak, Tetyana; Kosylova, Olga (Annals of Mechnikov's Institute, 2025)
The article presents a historical review of the I. I. Mechnikov Institute of Microbiology and Immunology of the National Academy of Medical Sciences of Ukraine. The I. I. Mechnikov Institute has come a long and storied historical path from the Kharkiv Pasteur Institute to the leading scientific institution in Ukraine. Its contribution to the development of microbiology and immunology in Ukraine and beyond is invaluable. The Institute has played a key role in combating many epidemics, developing vaccines and serums, and conducting cutting-edge scientific research. The scientific journal Annals of the Mechnikov Institute is an important platform for disseminating scientific knowledge in this field. The Institute’s extensive history, scientific achievements, and commitment to fighting infectious diseases highlight its significance for medical science and public health in Ukraine.